Establishing the Rationale for Media Education for Students in Ghana - Diedong, Africanus L.; Tuurosong, Damasus (Journal of Communications, Media & Society, 2018)
Recent developments in Information, Communication and Technologies (ICT) is propelling shifts in how important institutions such as the family, school and religion impart values to people, especially young persons. Arguably, these institutions seem to be losing their enviable positions as the main purveyors of values and wisdom in society. The paper argues for an overall rationale for media education in Ghana. Questionable contents of some media seem at variance with Ghanaian cultural values and norms within a context in which Media Education is taken for granted demands examination. In terms of methodology of the study, documents and other scientific research papers on Media Education were reviewed. A major finding of the study is that in Ghana there is no formal discourse about the need to integrate media education into curriculum. Therefore Media Education is yet to become a relevant course in the curricula of schools from the basic level of education to the second cycle through to the tertiary level. The paper concludes that Ghana can profit from a policy that establishes Media Education (ME) in her school system.
Research Article
Keywords: Information, Communication, Technologies, Ghana, Media Education, Students